Robustness evaluation of RC frame buildings to progressive collapse. (1st March 2015) - Fascetti, Alessandro; Kunnath, Sashi K.; Nisticò, Nicola
Highlights: A procedure is proposed for comparing the relative robustness of RC frames. Pushdown analyses are used in conjunction with time-history simulations. The method is validated by showing that the approach yields an ideal solution. Two robustness indices are defined. Abstract: A new procedure derived from non-linear static and dynamic analyses is proposed for comparing the relative robustness of RC frame buildings against progressive collapse. The methodology offers a formal way to assess the collapse resistance of structures following the sudden loss of one or more vertical load carrying member/s. The novelty of the proposed methodology lies in the sequential dynamic + static procedure that tracks the redistribution of axial forces following each critical column removal. The basic tool used in the procedure is the "pushdown" analysis, which permits estimation of the residual strength in the structure after it has been damaged by the loss of a critical vertical element. The proposed procedure identifies the critical sequence of column removals and is central to the methodology and the definition of the robustness indices. Referred to as Local Robustness Evaluation (LRE), the methodology is used to develop two robustness indices and applied to two buildings to demonstrate the effectiveness of the procedure in providing a basis for comparing their resistance to progressive collapse.